Jet momentum dependence of jet quenching in PbPb collisions at $\sqrt{s_{NN}}=2.76$ TeV - CMS collaboration (2198 authors) (2013)
Dijet production in PbPb collisions at a nucleon-nucleon center-of-mass energy of 2.76 TeV is studied with the CMS detector at the LHC. A data sample corresponding to an integrated luminosity of 150 inverse microbarns is analyzed. Jets are reconstructed using combined information from tracking and calorimetry. The dijet momentum balance and angular correlations are studied as a function of collision centrality and leading jet transverse momentum. For the most peripheral PbPb collisions, good agreement of the dijet momentum balance distributions with pp data and reference calculations at the same collision energy is found, while more central collisions show a strong imbalance of leading and subleading jet transverse momenta attributed to the jet-quenching effect. The dijet momentum imbalance in central collisions is found to persist for leading jet transverse momenta up to the highest values studied.